A double blind, randomised study of sildenafil citrate for erectile dysfunction in men with multiple sclerosis. Issue 5 (15th April 2005) - Fowler, C J; Miller, J R; Sharief, M K; Hussain, I F; Stecher, V J; Sweeney, M
Abstract : Objective: Identifying and effectively treating erectile dysfunction (ED) can result in an improvement of the quality of life (QoL) in men with multiple sclerosis (MS). Methods: This randomised, double blind (DB), placebo controlled, flexible dose study with an open label extension (OLE) assessed efficacy, QoL, and safety of sildenafil citrate in men with MS and ED. Overall, 217 men received sildenafil (25–100 mg; n = 104) or placebo (n = 113) for 12 weeks. Efficacy was assessed by the International Index of Erectile Function (IIEF) questionnaire that includes questions on achieving (Q3) and maintaining (Q4) an erection as well as a global efficacy question (GEQ). QoL was also assessed. Results: After 12 weeks, patients receiving sildenafil had higher mean scores for IIEF Q3 and Q4 compared with those receiving placebo (p<0.0001), and 89% (92/103) reported improved erections compared with 24% (27/112) of patients receiving placebo (p<0.0001). At the end of the OLE phase, 95% of men reported improved erections. Patients receiving placebo during the DB phase showed a nearly fourfold increase in improved erections (97% v 26%). Men receiving sildenafil also showed improvements in five of the eight general QoL questions compared with men receiving placebo (p<0.05). The total mean score for the QoL questionnaire improved by 43% for the sildenafil group versus 13% for the placebo group (p<0.0001). Treatment related AEs were predominantly mild in nature, and no patient discontinued due to an AE. Conclusion: Sildenafil treatment for ED in men with MS was effective and well tolerated, and resulted in significant improvements in both general and disease specific QoL variables.